Investigating male gamers' behavioral intention to play PUBG: Insights from playful-consumption experiences - Rehman, Umair; Shah, Muhammad Umair; Abbasi, Amir Zaib; Hlavacs, Helmut; Iftikhar, Rameen (Frontiers in Psychology, 2022)
This research investigates the factors that affect male gamers' behavioral intention to play PlayerUnknown's Battlegrounds (PUBG), which is one of the most widely played online game of today’s era. We examine the factors through the lens of hedonic consumption model (i.e. playful-consumption experiences) and uses and gratification theory to predict behavioral intention to play PUBG. Data from 248 male PUBG gamers were analyzed using PLS-SEM analyses. The study involved an initial stage where an estimation model (i.e. measurement model) was analyzed to assess the constructs' reliability and validity. Following this, the second stage involved assessing the theoretical model to test the relationship between the principle constructs. The study found that playful-consumption experience factors such as escapism, emotional involvement, sensory experience, enjoyment, and arousal, significantly influenced the behavioral intentions to play PUBG. The research findings further indicate that role-projection and fantasy failed to impact consumers' intention to play PUBG game. This study provides both theoretical and practical implications. It fills the literature gap by focusing on predicting the behavioral intention to play PUBG through the playful-consumption experiences of a popular online multiplayer game. Practically, this study could potentially open avenues for gaming companies to address how different playful-consumption experiences impact game users' behavioral intention.